The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1146/annurev-lawsocsci-101518-042717
|View full text |Cite
|
Sign up to set email alerts
|

Legal Consciousness Reconsidered

Abstract: Legal consciousness is a vibrant research field attracting growing numbers of scholars worldwide. Yet differing assumptions about aims and methods have generated vigorous debate, typically resulting from a failure to recognize that three different clusters of scholars—identified here as the Identity, Hegemony, and Mobilization schools—are pursuing different goals and deploying the concept of legal consciousness in different ways. Scholarship associated with these three schools demonstrates that legal conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 77 publications
1
115
0
5
Order By: Relevance
“…To reach a better understanding of how the meaning of legality is constituted through everyday practices, or rather the “cultural production” of hegemonic law (Silbey : 355–357), Silbey stresses the need to focus on the “middle level between citizen and the transcendent rule of law”; this space is embodied by social institutions such as the family unit, schools, corporations, or churches where the formation of cultural meaning, social hierarchy, and ultimately legal consciousness can be empirically observed (Miller ). However, although scholars agree that the focus should be on this middle level, not as much weight is placed on legal hegemony (Chua and Engel ; Liu ). When addressing the issue of law as a form of knowledge that serves as justification for what goes on in social transactions (Silbey and Sarat ), they rather suggest that more attention be put on the mutually constituted effect of law and identity that is connected to an individual's sense of self (Abrego , ; Chua and Engel ; Engel and Munger ; Hartog ; Tungnirun ), or how other norms, customary practices, or social positions influence the way individuals decide to mobilize their rights (Abrego ; Albiston ; Boittin ; Gallagher ; Marshall ).…”
Section: Exploring Legal Consciousnessmentioning
confidence: 99%
See 3 more Smart Citations
“…To reach a better understanding of how the meaning of legality is constituted through everyday practices, or rather the “cultural production” of hegemonic law (Silbey : 355–357), Silbey stresses the need to focus on the “middle level between citizen and the transcendent rule of law”; this space is embodied by social institutions such as the family unit, schools, corporations, or churches where the formation of cultural meaning, social hierarchy, and ultimately legal consciousness can be empirically observed (Miller ). However, although scholars agree that the focus should be on this middle level, not as much weight is placed on legal hegemony (Chua and Engel ; Liu ). When addressing the issue of law as a form of knowledge that serves as justification for what goes on in social transactions (Silbey and Sarat ), they rather suggest that more attention be put on the mutually constituted effect of law and identity that is connected to an individual's sense of self (Abrego , ; Chua and Engel ; Engel and Munger ; Hartog ; Tungnirun ), or how other norms, customary practices, or social positions influence the way individuals decide to mobilize their rights (Abrego ; Albiston ; Boittin ; Gallagher ; Marshall ).…”
Section: Exploring Legal Consciousnessmentioning
confidence: 99%
“…This emphasis on the role of identity in legal consciousness is magnified by Chua and Engel's () reasoning that an identity is inherently required for the law to be perceived and therefore plays a distinct role in determining how relevant the law is to an individual when faced with a conflict. Case studies carried out in North America (Engel and Munger ) and Thailand (Engel and Engel ) found that the formation of identity shapes legal consciousness, and vice versa, in a process that is not fixed but transformed throughout the course of one's life.…”
Section: Exploring Legal Consciousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…• identitātes skolu (Identity school) -izvirza hipotēzi, ka tiesiskā apziņa un identitāte rodas un veidojas viena no otras; • hegemonijas skolu (Hegemony school) -uzskata likumu par spēcīgu valsts kontroles instrumentu, kas veido indivīdu pasaules uzskatu, uztveri un lēmumus, turklāt pat tad, ja likums netiek piemērots tieši vai instrumentāli; • mobilizācijas skolu (Mobilisation school) -kontekstualizē tiesisko apziņu, lai izprastu likuma potenciālu pārveidot sabiedrību, īpaši taisnīguma panākšanas nolūkā [7]. Visos minētajos virzienos tiesiskā apziņa konceptuāli tiek saistīta ar elementiem, kas rodas sociālajā mijiedarbībā, respektīvi, -ar uzskatiem, uztveri un rīcību tiesību sfērā.…”
Section: Ievadsunclassified